Assisting the Development of Integrated Science Learning Tools Based on PjBL: Fostering Students’ Pancasila Character in the Merdeka Curriculum - Deswita, Pipi; Zamista, Adelia Alfama; Asrar, Allan; Fajri, Suryadi; Illahi, Rilci Kurnia; Hidayatul, Merlin; Lubis, Pauzan; Pratama, Redho (Universitas Lancang Kuning, 2023)
Merdeka Curriculum is a new curriculum implemented in Indonesia since 2022. After almost two years of implementation, curriculum implementers, especially teachers, are still in the adaptation stage of this curriculum. Even though the Ministry of Education has implemented various supporting programs for the successful implementation of the Merdeka Curriculum, such as the “guru penggerak” program, it turns out that not all teachers have the opportunity to take part in the program. So that in the learning process in the classroom there are still many teachers who experience difficulties. One of the main problems for teachers in implementing the Merdeka Curriculum is that teachers have never developed lesson plans in the form of teaching modules. Therefore, through community service (PkM), the service team conducted workshop in developing teaching modules for the Merdeka Curriculum for teachers who are members of the MGMP IPA MTs in Padang-Pariaman City. This PkM activity is carried out with a service learning approach. The result of this PkM activity is that teachers are able to develop teaching module templates which will be used as a basis for developing PjBL–based plans to strengthen the profile of Pancasila.